Assessments of mechanical stiffness and relationships to performance determinants in middle-distance runners - Rogers S. A.; Whatman, C. S.; Pearson, S. N.; Kilding, A. E. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To examine relationships between methods of lower-limb stiffness and their associations with running economy (RE) and maximal velocity (vmax) in middle-distance (MD) runners. Methods: Eleven highly trained male MD runners performed a series of mechanical and physiological tests to determine maximal overground sprint speed, RE, and V O 2 peak V.O2peak . Achilles tendon stiffness (kT) was estimated using ultrasonography during maximal isometric ankle plantar flexion. Global stiffness qualities were evaluated using a spring-mass model, providing measures of leg (kleg) and vertical stiffness (kvert) during running and jumping, respectively. Results: Very large (r=-.70) and large (r=-.60) negative relationships existed between RE and kT and kvert, during plantar flexion and unilateral jumps, respectively. There were large (r=.63) and extremely large (r=-.92) associations between kvert and kT and kleg during sprinting, respectively. Runners` vmax had large positive associations between kT (r=.52) and kleg (r=.59) during sprinting. Conclusions: In well-trained MD athletes, greater stiffness appears linked to faster and more economical running. Although kT had the strongest relationship with RE, kleg while sprinting and kvert in maximal unilateral jumps may be more practical measures of stiffness. Agreement between global stiffness assessments and kT highlights the energy contribution of the Achilles tendon to running efficiency and velocity. Further research incorporating these assessment tools could help establish more comprehensive mechanical and metabolic athlete profiles and further our understanding of training adaptations, especially stiffness modification, longitudinally.